A Case of a Paracardial Osteophyte Causing Atrial Compression - Stergios Tzikas; Konstantinos Triantafyllou; Christodoulos Papadopoulos; Vassilios Vassilikos (Case Reports in Medicine)
Osteophytes are pointed or beaked osseous outgrowths at the margins of articular surfaces that are often associated with degenerative changes of articular cartilage. They are the most common aspect of osteoarthritis and they infrequently cause symptoms by compression of the adjacent anatomic structures, such as nerves, vessels, bronchi, and esophagus. We present here a rare case of a patient with a left atrial deformation by a large osteophyte.